Transcription factor Meis1b regulates craniofacial morphogenesis in zebrafish - Psutkova, Viktorie; Nickl, Petr; Brezinova, Veronika; Machonova, Olga; Machon, Ondrej (Developmental dynamics, 2025)
BACKGROUND: Meis family of transcription factors operates in Pbx-Meis-Hox regulatory network controlling development of various tissues including eye, limbs, heart, hindbrain or craniofacial skeletal elements originating from the neural crest. Although studies in mouse provide abundant information about Meis factors function in embryogenesis, little is known about their role in zebrafish. RESULTS: We generated zebrafish lines carrying null mutations in meis1a, meis1b, meis2a, and meis2b genes. Only meis1b mutants are lethal at larval stage around 13 dpf whereas the other mutant lines are viable and fertile. We focused on development of neural crest-derived craniofacial structures such as tendons, cranial nerves, cartilage and accompanying muscles. Meis1b mutants displayed morphogenetic abnormalities in the cartilage originating from the first and second pharyngeal arches. Meckel's cartilage was shorter and wider with fused anterior symphysis and abnormal chondrocyte organization. This resulted in impaired tendons and muscle fiber connections while tenocyte development was not largely affected. CONCLUSIONS: Loss-of-function mutation in meis1b affects cartilage morphology in the lower jaw that leads to disrupted organization of muscles and tendons.
Keywords: chrupavka; Mutation; Homeodomain Proteins; zvířata; Gene Expression Regulation, Developmental; lebka; proteiny dánia pruhovaného; Zebrafish; Skull; Myeloid Ecotropic Viral Integration Site 1 Protein; vývojová regulace genové exprese; dánio pruhované; chondrocyte differentiation; morfogeneze; Morphogenesis; Cartilage; homeodoménové proteiny; Meis; zebrafish; Animals; crista neuralis; transkripční faktor Meis1; mutace; Neural Crest; craniofacial development; muscle fiber; Zebrafish Proteins